2017
DOI: 10.18203/2320-6012.ijrms20171229
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of oral itraconazole in the management of otomycosis with tympanic membrane perforation

Abstract: Background: Otomycosis can be a difficult problem to treat in a patient who already has a perforation of the tympanic membrane. This study highlights the effectiveness of oral Itraconazole in treating such cases.Methods: Thirty-four patients with otomycosis and a perforated tympanic membrane were included in the study and were treated with oral itraconazole and antibiotic ear drops. They were followed up for six weeks to look for treatment response and any recurrence.Results: Of the 34 patients in the study, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 6 publications
0
5
1
Order By: Relevance
“…Our results are inconsistent with those of other studies [ 2 , 5 , 21 , 25 ]. These differences can be due to the type of pathogenic etiological agents, anatomy of the ear, immune system status, and tympanic membrane perforation.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are inconsistent with those of other studies [ 2 , 5 , 21 , 25 ]. These differences can be due to the type of pathogenic etiological agents, anatomy of the ear, immune system status, and tympanic membrane perforation.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with our findings, in a single-blind randomized clinical study, 93.3% of the cases treated with clotrimazole and lignocaine solutions demonstrated an improvement in the clinical symptoms of itching and discharge, and ear pain was recovered in 86.7% of the patients [ 20 ]. In another study, Aju and Sagesh (2017) used a combination therapy with oral itraconazole and ofloxacin ear drops for the treatment of otomycosis [ 21 ] and reported similar results.…”
Section: Discussionmentioning
confidence: 92%
“…Other studies have also shown similar responses to clotrimazole and itraconazole in otomycosis. 24,25 Itraconazole is an effective alternative to a traditional method of treatment for otomycosis. 25 Compared to the study under discussion, different response to primary treatment was noted in several other studies.…”
Section: Discussionmentioning
confidence: 99%
“…Controversy exists between the types of antifungal ointment to be prescribed by otorhinolaryngologists. 11 We have compared nystatin versus isoconazole in present study. There is no previous study which has particularly compared these two antifungals.…”
Section: Discussionmentioning
confidence: 99%